Media in Republica Srpska: Audiences and content in context of uses and gratification theory - Vukojević, Borislav (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2015)
The media landscape of the Republika Srpska/Bosnia and Herzegovina is diverse, there are more than 180 registered media outlets: 44 television stations, 140 radio stations, three public broadcasting services, 9 daily newspapers and more than 100 magazines. On the other hand, the development of the Internet and new media has caused changes in the audience – they are no longer forced to be passive consumers of information. This paper explores the relationship of the audiences in the Republika Srpska towards print media, radio, television and the Internet. The relationship to the content and use in the context of the uses and gratification theory, agenda setting theory and theory of "framing" is further explored. The aim is to provide information on the media usage, such as readership of print newspapers, television viewership and audience relationship to the central news programs, dominant content in the media and media interests. The research hypothesis is that television is the dominant source for fullfiling the needs of media audiences, regardless of the growth of Internet and new media. The results obtained through quantitative analysis of public opinion polls on the basis of relevant scientific sample show that the most frequently used media is television; citizens more often prefer to watch informative contents, but they are aware that the media they follow are not working in their interest.